Investigating the impact of school principals’ role on quality of teaching and learning (A case study of a private school in Abu Dhabi) - ELARABY, TAMER (2019)
This research investigates the effective role that school principal plays in improving the school at all levels, especially improving the quality of teaching and learning which leads to improve students’ achievements. It also shows the roles and responsibilities of the current school principal and the different leadership styles that he applies in his school. It illustrates the impact of the school principal on teaching and learning and how he can address all the challenges that he faces in an MoE private school in Abu Dhabi. The research also shows the impact of the relationship between the school principal and teachers on the quality of teaching and students learning. It also illustrates the forms of support that the school principal provides to everyone in the school community and its impact on the quality of teaching and learning. The researcher prepared the research Statements and the survey Statements in a way that meets all challenges that the principal faces, as well as the roles and responsibilities of the school principal in raising the quality of teaching and learning and students’ achievements. For accordance and completeness purpose, the researcher used the triangulation method in the research. A survey (quantitative data) was sent to 70 teachers in the school, also there were some structured interviews with some teachers, some parents and some students in order to get feedback about the school performance at all levels and their opinion about the school principal in particular. The researcher received 55 responses out of 70 teachers. The data analysis process showed that, the positive relationships between the school principal and all the stakeholders in the school such as, teachers, students, parents, middle leaders, etc… has an effective impact on the quality of teaching and learning, teachers’ motivation, students readiness to learn as well as parents satisfaction. It also showed that the school principal has a direct impact on students’ achievements and teachers’ performance. Moreover, the school principal supported the school at all levels in order to address all the difficulties and challenges that face teachers, students and even parents, for example, the students come from different nationalities, and the school leadership team managed to make the school a model example of the peaceful coexistence. At the end of the study, the researcher presented some recommendations for the school principal in order to move the school forward and meet the standards of the good schools according to the UAE Inspection Framework.